2015
DOI: 10.1038/srep15089
|View full text |Cite
|
Sign up to set email alerts
|

Width-controlled M-type hexagonal strontium ferrite (SrFe12O19) nanoribbons with high saturation magnetization and superior coercivity synthesized by electrospinning

Abstract: Width-controlled M-type hexagonal SrFe12O19 nanoribbons were synthesized for the first time via polyvinylpyrrolidone (PVP) sol assisted electrospinning followed by heat treatment in air, and their chemical composition, microstructure and magnetic performance were investigated. Results demonstrated that as-obtained SrFe12O19 nanoribbons were well-crystallized with high purity. Each nanoribbon was self-assembled by abundant single-domain SrFe12O19 nanoparticles and was consecutive on structure and uniform on wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(32 citation statements)
references
References 59 publications
3
29
0
Order By: Relevance
“…Moreover, nanoribbons also could be considered as a development by cutting a finite-width slice from the 2D nanosheets. In this context, width-controlled SrFe 12 O 19 (strontium ferrite) nanoribbons were synthesized via a polymer sol-assisted single-spinneret electrospinning route followed by heat treatment in air (Jing et al 2015).…”
Section: Nanoribbonmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, nanoribbons also could be considered as a development by cutting a finite-width slice from the 2D nanosheets. In this context, width-controlled SrFe 12 O 19 (strontium ferrite) nanoribbons were synthesized via a polymer sol-assisted single-spinneret electrospinning route followed by heat treatment in air (Jing et al 2015).…”
Section: Nanoribbonmentioning
confidence: 99%
“…7e). Subsequently, the (Jing et al 2015) jet is subjected to an unstable stage with a series of bending instabilities and anisotropic shrinkage and is finally elongated with or without branching/splitting and solidified to PVP/SrFe 12 O 19 composite precursor nanoribbons (Fig. 7f).…”
Section: Nanoribbonmentioning
confidence: 99%
“…Nanoribbons could also be regarded as a development by cutting a finite-width slice from the two-dimensional nanosheets. In recently works, we have demonstrated that the electrospun SrFe 12 O 19 and CoFe 2 O 4 nanoribbons both exhibited deeply impressed magnetic properties2224. To the best of our knowledge, there is still no public report on Fe-Ni alloy nanoribbons.…”
mentioning
confidence: 99%
“…Earlier reports have certified that nanofibers20, nanotubes21 and nanoribbons22 could be directly obtained via the electrospinning route combined with a series subsequent treatments, and that all of these 1D nanostructures were tens of micrometers in length and their diameters or width can be flexibly tuned from nanometers to micrometers. To date, however, only Lee et al .…”
mentioning
confidence: 99%
“…Among various advanced magnetic nano materials, M-type hexaferrite with chemical formula of MeFe 12 O 19 (Me=Sr, Ba and Pb) had demonstrated to be an important class of magnetic materials. For vast scientific and technological interests these ferrites have emerged as multifunctional materials due to the stability of their properties [4]. In 1950's, a classical hard magnetic material, strontium ferrite (SrFe 12 O 19 ) was discovered.…”
Section: Introductionmentioning
confidence: 99%